2015
DOI: 10.1111/jfb.12650
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal isotopic signatures (δ13C and δ15N) reveal that two sympatric West African mullet species do not feed on the same basal production sources

Abstract: Potential trophic competition between two sympatric mullet species, Mugil cephalus and Mugil curema, was explored in the hypersaline estuary of the Saloum Delta (Senegal) using δ13C and δ15N composition of muscle tissues. Between species, δ15N compositions were similar, suggesting a similar trophic level, while the difference in δ13C compositions indicated that these species did not feed from exactly the same basal production sources or at least not in the same proportions. This result provides the first evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Resource partitioning has been reported for many fish species, and in diverse types of estuaries, including tropical ones (Pimentel and Joyeux, 2010;Le Loc'h et al, 2015;Moulton et al, 2017;Stevens et al, 2020). In the three estuaries studied here, although the two jack species had very similar prey and isotopic niches in overall, they exhibited slight spatial differences in their diet composition, which contributed to reduce the actual overlap in their niches at each studied location.…”
Section: Possibility For Trophic Competitionmentioning
confidence: 62%
“…Resource partitioning has been reported for many fish species, and in diverse types of estuaries, including tropical ones (Pimentel and Joyeux, 2010;Le Loc'h et al, 2015;Moulton et al, 2017;Stevens et al, 2020). In the three estuaries studied here, although the two jack species had very similar prey and isotopic niches in overall, they exhibited slight spatial differences in their diet composition, which contributed to reduce the actual overlap in their niches at each studied location.…”
Section: Possibility For Trophic Competitionmentioning
confidence: 62%
“…In general, these specimens were collected from Laguna Madre Lagoon (Figure 4i,j), which can reach salinities of greater than 60 (Table 1). The use of hypersaline environments was previously reported in other areas, such as the Saloum Delta (Senegal), where salinities can reach 55 (Le Loc'h et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…Ecological studies have found that in southeastern Brazil, M. curema is associated with high salinity waters while M. liza is associated with lower salinity (Mai et al 2018 ), suggesting some ecological isolation between these species. Diet studies have shown that sympatric species of Mugil in West Africa can present differential particle size selection to avoid competition (LeLoc’h et al 2015 ), possibly constituting a further ecological isolating barrier. Furthermore, cytogenetic studies have shown that some of these species differ in the number and arrangement of chromosomes (Rossi et al 2005 ; Harrison et al 2007 ; Nirchio et al 2017 ), possibly constituting a genetic isolating barrier.…”
Section: Discussionmentioning
confidence: 99%